2013
DOI: 10.1080/10586458.2013.748379
|View full text |Cite
|
Sign up to set email alerts
|

Three-Step and Four-Step Random Walk Integrals

Abstract: We investigate the moments of 3-step and 4-step uniform random walk in the plane. In particular, we further analyse a formula conjectured in [BNSW09] expressing 4-step moments in terms of 3-step moments. Diverse related results including hypergeometric and elliptic closed forms for W 4 (±1) are given and two new conjectures are recorded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 15 publications
1
53
0
Order By: Relevance
“…Integrals such as (4) are the s-th moment of the distance to the origin after n steps. In [77], it is shown that when s = 0, the first derivatives of these integrals, which arise independently in the study of Mahler measures, are…”
Section: Ramble Integralsmentioning
confidence: 99%
“…Integrals such as (4) are the s-th moment of the distance to the origin after n steps. In [77], it is shown that when s = 0, the first derivatives of these integrals, which arise independently in the study of Mahler measures, are…”
Section: Ramble Integralsmentioning
confidence: 99%
“…We note that, as in [BSW13], this Meijer G-function expression can be expressed as a sum of hypergeometric functions by Slater's Theorem [Mar83,p. 57].…”
Section: Moments Of 3-step Walksmentioning
confidence: 99%
“…As much as possible, we keep our notation consistent with that in [BNSW11,BSW13], and especially [BSWZ12], to which we refer for details of how to exploit the Mellin transform and similar matters. Random walks in higher dimensions are also briefly discussed in [Wan13,Chapter 4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These Meijer-G functions, first introduced in 1936, also occur in quantum field theory and many other places [8]. For example, the moments of an n-step random walk in the plane are given for s > 0 by It transpires [24], [36] that for all complex s (6) Example 9 (Trefethen's problem #10 [16], [19]). A particle at the center of a 10 × 1 rectangle undergoes Brownian motion (i.e., 2-D random walk with infinitesimal step lengths) till it hits the boundary.…”
Section: Example 7 (Trefethen Problem #2 [16] [19])mentioning
confidence: 99%